Heterogeneous Effects of Housing Vouchers on the Mental Health of US Adolescents. - Nguyen, Quynh C.; Rehkopf, David H.; Schmidt, Nicole M.; Osypuk, Theresa L. (American Journal of Public Health, 2016)
Objectives. To assess the mental health effects on adolescents of low-income families residing in high-poverty public housing who received housing vouchers to assist relocation. Methods. We defined treatment effects to compare 2829 adolescents aged 12 to 19 years in families offered housing vouchers versus those living in public housing in the Moving to Opportunity experiment (1994-1997; Boston, MA; Baltimore, MD; Chicago, IL; Los Angeles, CA; New York, NY). We employed model-based recursive partitioning to identify subgroups with heterogeneous treatment effects on psychological distress and behavior problems measured in 2002. We tested 35 potential baseline treatment modifiers. Results. For psychological distress, Chicago participants experienced null treatment effects. Outside Chicago, boys experienced detrimental effects, whereas girls experienced beneficial effects. Behavior problems effects were null for adolescents who were aged 10 years or younger at baseline. For adolescents who were older than 10 years at baseline, violent crime victimization, unmarried parents, and unsafe neighborhoods increased adverse treatment effects. Adolescents who were older than 10 years at baseline without learning problems or violent crime victimization, and whose parents moved for better schools, experienced beneficial effects. Conclusions. Health effects of housing vouchers varied across subgroups. Supplemental services maybe necessary for vulnerable subgroups for whom housing vouchers alone may not be beneficial.